How Civilian Attitudes Respond to the State's Violence: Lessons from the Israel- Gaza Conflict - Amit Loewenthal; Sami H. Miaari; Alexei Abrahams (Institute of Labor Economics (IZA), 2021)
States, in their conflicts with militant groups embedded in civilian populations, often resort to policies of collective punishment to erode civilian support for the militants. We attempt to evaluate the efficacy of such policies in the context of the Gaza Strip, where Israel's blockade and military interventions, purportedly intended to erode support for Hamas, have inflicted hardship on the civilian population. We combine Palestinian public opinion data, Palestinian labor force surveys, and Palestinian fatalities data, to understand the relationship between exposure to Israeli policies and Palestinian support for militant factions. Our baseline strategy is a difference-in-differences specification that compares the gap in public opinion between the Gaza Strip and the West Bank during periods of intense punishment with the gap during periods when punishment is eased. Consistent with previous research, we find that Palestinian fatalities are associated with Palestinian support for more militant political factions. The effect is short-lived, however, dissipating after merely one quarter. Moreover the blockade of Gaza itself appears to be only weakly associated with support for militant factions. Overall, we find little evidence to suggest that Israeli security policies towards the Gaza Strip have any substantial lasting effect on Gazan support for militant factions, neither deterring nor provoking them relative to their West Bank counterparts. Our findings therefore call into question the logic of Israel's continued security policies towards Gaza, while also raising the possibility more generally that populations violently targeted by state actors may exhibit greater inertia in their support for militancy (or lack thereof) than is typically theorized in standard models of deterrence.
Keywords: D72; D74; H56; J21; J45; 330; Israeli-Palestinian conflict; political preferences; public opinion; conflict; Palestine